Artificial pollination in acung (Amorphophallus decus-silvae Back. & v.A.v.R.) - MADE SRI PRANA (Biodiversitas Journal of Biological Diversity, 2008)
A study was conducted on artificial pollination, both self and cross pollinations, of Amorphophallus decus-silvae Back. & v.A.v.R. planted in a house yard in Bogor. It was observed that no fruit set was resulted from self pollination. On the other hand cross pollination successfully produced numerous fruits. It was suggested that phenomena was due to protogenic character rather than self incompatibility mechanism of the species. The stigmas mature 1-2 days earlier than the anthers (pollen shedding). Such a case was also reported earlier by otherauthors in A. titanium Becc.Key words: acung, Amorphophallus decus-silvae Back. & v.A.v.R., pollination, fertilization, fruit, seed.